HEART RETRANSPLANTATION - R. Sh. Saitgareev; V. M. Zakharevich; A. M. Golts; T. A. Khalilulin; D. V. Borisov (Вестник трансплантологии и искусственных органов, 2016)
The number of patients with transplanted heart is continuously increasing; therefore, the number of patients requiring heart retransplantation grows. Analysis of the results of published studies focused on safety of cardiac retransplantation and risk factors for adverse events in perioperative, early and late postoperative periods is presented in our review. The results of published studies suggest that heart retransplantation is the main radical treatment option for cardiac allograft dysfunction, but the results of heart retransplantation are slightly worse than those of primary cardiac transplantation. On the other hand, the favorable long-term prognosis after heart retransplantation should be expected in carefully selected recipients.